Crohn's disease and environmental contamination: Current challenges and perspectives in exposure evaluation. (August 2020) - Tenailleau, Quentin M.; Lanier, Caroline; Gower-Rousseau, Corinne; Cuny, Damien; Deram, Annabelle; Occelli, Florent
Abstract: Although the incidence of Crohn's disease has increased worldwide over the past 30 years, the disorder's exact causes and physiological mechanisms have yet to be determined. Given that genetic determinants alone do not explain the development of Crohn's disease, there is growing interest in "environmental" determinants. In medical science, the term "environment" refers to both the ecological and social surroundings; however, most published studies have focused on the latter. In environmental and exposure sciences, the term "environment" mostly relates to contamination of the biotope. There are many unanswered questions on how environmental hazards might contribute to the pathogenesis of Crohn's disease. Which pollutants should be considered? Which mechanisms are involved? And how should environmental contamination and exposure be evaluated? The objective was to perform a systematic review of the literature on Crohn's disease and environmental contamination. We searched the PubMed, Google Scholar, Scopus, ISI Web of Science and Prospero databases. We considered all field studies previous to April 2019 conducted on human health indicators, and evaluating exposure to all type of physical, biological and chemical contamination of the environment. The lack of clear answers to date can be ascribed to the small total number of field studies (n = 16 of 39 publications, most of which were conducted by pioneering medical scientists), methodological differences, and the small number of contaminants evaluated. This make it impossible to conduct a coherent and efficient meta-analysis. Based on individual analysis of available studies, we formulated five recommendations on improving future research: (i) follow up the currently identified leads - especially metals and endocrine disruptors; (ii) explore soil contamination; (iii) gain a better knowledge of exposure mechanisms by developing transdisciplinary studies; (iv) identify the most plausible contaminants by developing approaches based on the source-to-target distance; and (v) develop registries and cohort-based analyses. Graphical abstract: Image 1 Highlights: The first systematic review of environmental contamination and Crohn's disease. The few field studies had differing methodologies and conflicting results. Metals and endocrine disruptors are potential candidates. A source-to-target-distance-based approach might highlight new candidate pollutants. Soil contamination should always be investigated for chronic diseases.